Measuring material deprivation in the enlarged EU - Christopher T. Whelan; Brian Nolan; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2008)
This paper uses new data from EU-SILC for twenty-six European countries to examine the structure and distribution of material deprivation in the enlarged EU. We identify three distinct dimensions of material deprivation relating to consumption, household facilities and neighbourhood environment, and construct indices of these dimensions for each country and the EU as a whole. The extent of variation across countries and welfare regimes is shown to depend on the dimension on which one focuses, as does the strength of the association with household income and subjective economic stress. The index of consumption deprivation has by far the highest correlation with income, provides a highly reliable measure in itself, and allows segments of the population to be identified that are sharply differentiated in terms of their multi-dimensional deprivation profiles. On the basis of this evidence we make some suggestions as to the manner in which the measurement of material deprivation in the European Union should be developed through the proposed special module of deprivation which will form part of the 2009 wave of EU-SILC.
Keywords: 330; Armut; Haushaltseinkommen; Soziale Lage; Randgruppe; EU-Staaten